Optimal Model Selection in RDD and Related Settings Using Placebo Zones - Nathan Kettlewell; Peter Siminski (Institute of Labor Economics (IZA), 2020)
We propose a new model-selection algorithm for Regression Discontinuity Design, Regression Kink Design, and related IV estimators. Candidate models are assessed within a 'placebo zone' of the running variable, where the true effects are known to be zero. The approach yields an optimal combination of bandwidth, polynomial, and any other choice parameters. It can also inform choices between classes of models (e.g. RDD versus cohort-IV) and any other choices, such as covariates, kernel, or other weights. We use the approach to evaluate changes in Minimum Supervised Driving Hours in the Australian state of New South Wales. We also re-evaluate evidence on the effects of Head Start and Minimum Legal Drinking Age. We conclude with practical advice for researchers, including implications of treatment effect heterogeneity.
Keywords: C13; C52; I18; 330; regression discontinuity; regression kink; graduated driver licensing